1983
DOI: 10.1073/pnas.80.10.2854
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody to chicken oviduct progesterone receptor.

Abstract: Antibodies to molybdate-stabilized chicken oviduct progesterone receptor were raised in a Wistar rat and detected by interaction with homogeneous radioiodinated progesterone receptor. Spleen cells of this rat were then fused with mouse Sp2/0-Agl4 myeloma cells and the antibodies produced by the hybrid cells were detected by double immunoprecipitation using the '5I-labeled receptor. Cells of one of the positive cultures were then cloned by limiting dilution and one hybridoma cell line was studied. The monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

1983
1983
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…In all cases, 8.6S complexes were shifted to ~ 1 IS after interaction with the BF4 mono clonal antibody [16], confirming the pres ence of hsp 90 [21]. TA-GR complexes, in absence of molybdate, shifted to 4.4S after exposure to transforming ionic strength or temperature.…”
Section: Generalities and Complexitysupporting
confidence: 52%
See 1 more Smart Citation
“…In all cases, 8.6S complexes were shifted to ~ 1 IS after interaction with the BF4 mono clonal antibody [16], confirming the pres ence of hsp 90 [21]. TA-GR complexes, in absence of molybdate, shifted to 4.4S after exposure to transforming ionic strength or temperature.…”
Section: Generalities and Complexitysupporting
confidence: 52%
“…If the extrac tion is performed with high ionic strength buffer (usually >0.25 M KC1), or if second arily the 8S-R is exposed to such a salt-con taining medium, the hormone-binding peak sediments with a ~4 S sedimentation coeffi cient (4S-R). Hormone affinity chromatogra phy purification has been performed on this premise, and thanks to the stabilizing effect of molybdate ions [11][12][13], the 8S-R form of the progesterone receptor, not binding to DNA-cellulose, was isolated [14], while the purified hormone-binding, DNA-binding 4S-R was also obtained in relatively good yield [15], A monoclonal antibody to 8S-PR [16] was found to detect a nonhormone binding, non-DNA-binding, MW ~ 90,000 superscript asterisk indicates that the receptor is ac tive. We have shown, by drawing a one-way arrow, that a practically irreversible transconformalion takes place after release of H R' from hsp, which might explain the difficulty to recombine H-R* with hsp.…”
Section: Generalities and Complexitymentioning
confidence: 99%
“…Radanyi et a1 [24] prepared a monoclonal antibody (BF4) to the purified, molybdate-stabilized chicken oviduct progesterone receptor and showed that it reacted with the 90 kD nonsteroid-binding protein but not with the 80 kD or the 110 kD progesterone-binding proteins [25]. Similarly, antiserum raised against the purified 110 kD progesteronebinding protein recognizes the 80 and 110 kD steroid-binding peptides but not the 90 kD peptide [26].…”
Section: Complexesmentioning
confidence: 99%
“…The second biotinylated antibody, PR22 (PR-IEMA) or 7Da (PR-hsp90 complex IEMA), and peroxidase-labeled avidin were added. During all incubations, 20 both receptor-free and receptor-bound chsp90 (19,20,25). Staining of chsp90 was specific, since no staining was seen when the antibody was replaced by either buffer or nonspecific antibodies or when the specific antibodies were presaturated with an excess of affinity-purified chsp90 (Fig.…”
mentioning
confidence: 99%
“…Fixation with p-benzoquinone or formaldehyde vapor gave essentially similar results. Polyclonal antibody IgGRB (17); monoclonal antibodies PR6, PR13, and PR22 (18) against affinity-purified PR; and monoclonal antibodies BF4, 7Da, and 4F3 against hsp90 (19,20) Cytosols and Nuclear Extracts. These were prepared as described (10,11).…”
mentioning
confidence: 99%